A criminological Study on the Difficulties of The Suspect Kept in Remand Prison for Long Periods - Hewawasam, H.P.K.N. (My University, 2017)
Attached

This study is based on the cases with much social attention for long time detention of suspects. It is also developed on the cases of detaining male suspects more than one year. In certain occasions, suspected individuals are sentenced less than one- year imprisonments. The ultimate problem is that the suspect is still not proved as guilty. It is a considerable problem that a person who is not found guilty is kept in a remand jail. Accordingly, the central problem of this research study is to understand the nature of socio – economic background of male suspects those who are kept in custody for more than one year. The sample limit had taken as the only male suspects those who are kept more than one year in new Magazine prison. As the sample 110 male suspects were randomly selected for the purpose of this research study. First is the primary source, qualitative information obtained through methods of interview and questionnaire and observations. Data analysis was done in quantitative and qualitative approach. The following facts were derived from the research. Keeping suspects in the custody for longer periods were a threat to their physical and mental wellbeing. It was also learned that the fewer facilities and overcrowding of prisons, cause mental and physical difficulties among these male suspects. Isolation from the relatives as a result of long time detention was one major problem for them. Total separation from the family environment for a long period of time had resulted in weaker psychological conditions. It was obvious that the weaknesses of criminal justice system cause to kept suspects in remand prison for long periods. One of the main reasons for this delay was delaying of the reports from Government Analysts Department. According to the research, accelerating the criminal justice system improving the methods and efficiency of investigations, considering the background of the suspects when calling for financial bonds and reforming the law on personal bonds could be proposed.
Keywords: Male Suspects, Remand Prison, Analysts'report, Bonds, Witnesses